v=x(18-2x)(9-2x)

Simple and best practice solution for v=x(18-2x)(9-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v=x(18-2x)(9-2x) equation:


Simplifying
v = x(18 + -2x)(9 + -2x)

Multiply (18 + -2x) * (9 + -2x)
v = x(18(9 + -2x) + -2x * (9 + -2x))
v = x((9 * 18 + -2x * 18) + -2x * (9 + -2x))
v = x((162 + -36x) + -2x * (9 + -2x))
v = x(162 + -36x + (9 * -2x + -2x * -2x))
v = x(162 + -36x + (-18x + 4x2))

Combine like terms: -36x + -18x = -54x
v = x(162 + -54x + 4x2)
v = (162 * x + -54x * x + 4x2 * x)
v = (162x + -54x2 + 4x3)

Solving
v = 162x + -54x2 + 4x3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Simplifying
v = 162x + -54x2 + 4x3

See similar equations:

| 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k | | (2/3)x-(1/6)=(2/7) | | d=85t+340 | | 3(3*x+4*y+5)+2(2*x-4*y-3)=z | | 2x=4x+18 | | 6-5(3x-2)=-14 | | X+.25X=45 | | 16x-5=2(2x+3) | | -149=10x-29 | | 4/(-1)-5 | | 6=(y-10) | | 4/(-1) | | (3x-2/4)+(x+57/7)=13 | | x4/x=2 | | 30=90/x | | (9-2y)/3=y | | 6-6r-2=16 | | 30=90 | | 3(3*x+4*y+5)+2(2*x-4*y-3)= | | 3x-2/4+x+57/7=13 |

Equations solver categories